(untitled) - Smith, Adam (New York, 1930)
Adam Smith's The Wealth of Nations was recognized as a landmark of human thought upon its publication in 1776. As the first scientific argument for the principles of political economy, it is the point of departure for all subsequent economic thought. Smith's theories of capital accumulation, growth, and secular change, among others, continue to be influential in modern economics.
Keywords: Kinh tế học,Economics